Serum soluble interleukin-2 receptor level is a predictive marker for EBUS-TBNA-based diagnosis of sarcoidosis - Miyata, Jun; Ogawa, Takunori; Tagami, Yoichi; Sato, Takashi; Nagayama, Mikie; Hirano, Toshiyuki; Kameyama, Naofumi; Fukunaga, Koichi; Kawana, Akihiko; Inoue, Takashi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a widely available diagnostic tool for suspected stage I/II sarcoidosis. Combination of EBUS-TBNA and transbronchial lung biopsy (TBLB) has been proposed as diagnostic procedure in clinical settings. Objectives: The aim of this study was to assess the diagnostic yield of combined EBUS-TBNA and TBLB and identify the markers correlated with a high diagnostic rate. Methods: We retrospectively analyzed the data of 37 patients with suspected stage I/II sarcoidosis with enlarged hilar or mediastinal lymph nodes on computed tomography (CT) images. These patients had been scheduled to undergo EBUS-TBNA and TBLB. Serum levels of sarcoidosis markers (angiotensin-converting enzyme [ACE], soluble interleukin-2 receptor [sIL-2R], and lysozyme), CT findings, and examination techniques were evaluated as predictive markers for diagnosis. Results: Of the 37 patients, 32 had undergone both EBUS-TBNA and TBLB, while the remaining 5 patients had only undergone EBUS-TBNA. The diagnosis was confirmed by TBLB in 16 of the 32 patients (50.0%), EBUS-TBNA in 31 of the 37 patients (83.8%), and combined TBLB and EBUS-TBNA in all patients (100.0%). The serum level of sIL-2R, but not that of ACE or lysozyme, was correlated with successful diagnosis by EBUS-TBNA. Conclusion: In patients with stage I/II sarcoidosis, the serum level of sIL-2R is a promising and useful marker for predicting the diagnosis by EBUS-TBNA and reducing the burden of additional TBLB and its possible complications.